Comparison between the panoptic ophthalmoscope and the conventional direct ophthalmoscope in the detection of sight threatening diabetic retinopathy: the Kuching diabetic eye study - Tan, A.K; Mallika, P.S; Aziz, S.; Asok, T.; Intan, G.; H.A, Faridah (Academy of Family Physicians of Malaysia, 2010)
AK Tan, PS Mallika, S Aziz, T Asokumaran, G Intan HA Faridah